Numerical Algebra, Matrix Theory, Differential-Algebraic Equations and Control Theory (Festschrift in Honor of Volker Mehrmann) - Benner, Peter (Springer, 2015)
This book is dedicated to Volker Mehrmann, our mentor, co-author, colleague, and friend. Each chapter in this book highlights one of the many topics Volker has worked on. Inevitably, there are omissions. In this preface, we therefore make an attempt to not only connect the book chapters to Volker’s bibliography but to also provide additional details on topics that receive less attention in the subsequent chapters.